Cytotoxic Activity of Holothuria leucospilota Extract against Leishmania infantum In Vitro - Shahram Khademvatan; Alborz Eskandari; Jasem Saki; Masoud Foroutan-Rad (Hindawi Limited, 2016)
Leishmaniasis is a tropical parasitic infection. The resistance and toxicity issues are the major complications and remain significant consequences related to the treatment of leishmaniasis with the recent and classical drugs. Thus there is an immediate requirement to develop new compounds for the treatment of this protozoan disease. Sea cucumbers or holothurians are potentially presented as the marine sources of antimicrobial and cytotoxic compounds. The aim of this study was investigation of in vitro antileishmanial activity of methanol extract of body wall, coelomic fluid, and cuvierian organs of Holothuria leucospilota obtained from coastal parts of Persian Gulf against Leishmania infantum promastigotes and axenic amastigotes. The colorimetric MTT assay was used to determine L. infantum promastigotes and axenic amastigotes viability at different concentrations of the extracts and drug control (Glucantime®) at time dependent manner and the results are represented as IC50 (50% of inhibitory concentration). Coelomic fluid was the most active extract among the three different extracts of H. leucospilota against L. infantum promastigotes and axenic amastigotes with IC50s of 62.33 μg/mL and 22.4 μg/mL and 73 μg/mL and 46 μg/mL at 48 and 72 hours after treatment, respectively. Cuvierian organs extract showed less toxicity with IC50s more than 1000 μg/mL for both Leishmania infantum axenic amastigotes and promastigotes forms after 48 and 72 hours of exposure. Results acquired from the present study propose that the sea cucumber H. leucospilota may be a provoking source of antileishmanial compounds and could be a lead source in the development of the potent antileishmanial and cytotoxic drugs.